Efficacy comparative characteristics of antiseptic DECASAN Yuria-Pharm and CUTASEPT G in the treatment of purulent inflammatory diseases of various localization (Perioperaciina Medicina, 2021)
Background: High mortality because of various infectious complications (immediate cause in 42.5 % of cases), the ever-increasing frequency of purulent inflammatory diseases, as well as the growth of microbial resistance to anti-bacterial drugs, force to seek a solution to the problem among local antiseptics. Aim: to compare the effectiveness of antiseptics DECASAN Yuria-Pharm and CUTASEPT G in the treatment of puru-lent inflammatory diseases of different localization.Materials and methods: The study involved 30 patients with purulent inflammatory diseases of various localiza-tions. Patients were divided into two groups, according to the chosen tactics of local antiseptic therapy, in patients of the first study group (n = 15; mean age – 49.73 ± 6.35 years) antiseptic treatment was performed with a drug based on 0.02 % decamethoxine (Decasan). In the second group (n = 15; mean age – 51.4 ± 5.14 years) treatment was performed with a disinfectant (skin antiseptic) “Cutasept G”. Collection of material for microbiological examination (bacteriological culture) was performed before treatment, 3 and 5 days after treatment. Probability analysis was performed according to Student’s t-test. A statistically significant difference between the indicators was considered when the probability of validity of the null hypothesis was less than 5 % (p
Keywords: Decametoxine; purulent inflammatory diseases; S. aureus; Ps. aeruginosa; antibiotic resistance